The effectiveness of mindfulness application "SI-SIWATA (Sistem Informasi Sehat Jiwa dengan Cinta) to increase the spirituality of schizophrenia patients: Experimental study - Agustriyani, Feri; Dwidiyanti, Meidiana; Suerni, Titik (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Spirituality is an important aspect in human life and individuals with schizophrenia are no exception, where the problem of spirituality in schizophrenia patients can be handled with spiritual mindfulness psychotherapy which is currently starting to be developed based on an android application. The purpose of this study was to determine the effect of spiritual mindfulness interventions through the android application SI-SIWATA on the spirituality of schizophrenic patients. This research is a quasi-experimental study with a sampling technique using purposive sampling. The sample in this study was 46 schizophrenic patients divided into intervention and control groups. Spiritual mindfulness intervention was carried out six times and was carried out pre-test and post-test using the Daily Spiritual Experience Scale questionnaire and analyzed using paired sample t-test. Statistical test results show the p-value = 0,001 (less than 0.05) it means that there is an influence of spiritual mindfulness interventions on the spirituality of schizophrenic patients. An increase in patient spirituality was related to the emphasis on the mindfulness intervention stage, namely the muhasabah (introspection) stage and the independent healthy target stage so, the patient can consciously understand the conditions experienced, accept the treatment process and perform the independent healthy target in worship. Spirituality independence is very important in helping patients growing faith in Allah SWT when undergoing the treatment process.Peningkatan spiritualitas  pasien skizofrenia dengan mindfulness melalui aplikasi SI-SIWATA (Sistem Informasi Sehat Jiwa Dengan Cinta)AbstrakSpiritualitas merupakan aspek penting dalam kehidupan manusia, tidak terkecuali individu dengan skizofrenia dimana masalah spiritualitas pasien skizofrenia dapat ditangan dengan psikoterapi mindfulness spiritual yang saat ini mulai dikembangkan dengan berbasis aplikasi android. Tujuan penelitian ini untuk mengetahui pengaruh intervensi mindfulness spiritual melalui aplikasi android SI-SIWATA terhadap spiritualitas pasien skizofrenia. Penelitian ini merupakan penelitian quasi-eksperimental dengan tehnik pengambilan sampel menggunakan purposive sampling. Sampel pada penelitian ini berjumpal 46 pasien skizofrenia yang dibagi dalam kelompok intervensi dan kelompok kontrol. Intervensi mindfulness spiritual dilakukan selama enam kali dan dilakuakn pre-test dan post-test menggunakan kuesioner Daily Spiritual Experience Scale dan dianalisis menggunakan paired sample t test. Hasil uji statistic menunjukan nilai p = 0,001 (kurang dari 0,05) artinya ada pengaruh intervensi mindfulness spiritual terhadap spiritualitas pasien skizofrenia.  Adanya peningkatan spiritualitas pasien berhubungan dengan penekanan tahapan intervensi mindfulness yaitu tahapan muhasabah dan tahap target sehat mandiri, sehingga pasien secara sadar mampu memahami kondisi yang dialami, menerima proses pengobatan dan melakukan target sehat mandiri dalam beribadah. Kemandirian spiritualitas sangat penting dalam membantu pasien menumbuhkan keyakinan kepada Allah SWT dalam menjalani proses perawatan.